The Effect Of Cooperative Learning Model Type Of Teams Games Tournament (Tgt) On Student's Learning Achievement - Nurun Najmi; Muhammad Husnur Rofiq; Muhammad Anas Maarif (At-Tarbiyat, 2021)
The purpose of this learning is to find out the cooperative learning model type Teams Games Tournament (TGT) on student achievement in Fiqh subjects at Mts Ma'arif Bebandem. The method used is the Quasi Experimental Method. In this study, the research subjects were students of class VII A and VII B MTs Ma'arif Bebandem. Class VII A as the Control Class (Lecture) and VII B as the Experiment class (TGT). The instrument used is the learning achievement test instrument. The learning achievement test questions used were 25 questions in the form of multiple choice and after going through the validity test process. The findings of this study are the influence of the use of the cooperative learning model type Teams Games Tournament (TGT) on student Islamic Civilization History learning outcomes. This is shown from the results of hypothesis testing using t-test, the value of thitung = 9.956 is greater than ttabel = 2.019 with a significant level of 0.05 so that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. In addition, seen from the results of the comparison of the pre-test and post-test, the pre-test mean score obtained by the control class was 53.25 and the experimental class was 57.50, while the results of the post-test mean score The Team Games Tournament 87.50 type cooperative learning model shows a higher score compared to the control class using the Lecture / Conventional method 67.50. From the research that has been done, it can be concluded that the cooperative learning model type Teams games Tournament (TGT) has an effect on student achievement in Islamic Islamic Civilization History.